DESCENT RENEWAL AND SUSTAINABLE ENVIRONMENTAL CONSERVATION IN THE PERSPECTIVE OF ISLAMIC EDUCATIONAL PSYCHOLOGY - Marilini, Dewi Ayu; Aminullah (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2024)
This research aims to examine the urgency and strategy of hereditary renewal and sustainable environmental conservation in the perspective of Islamic educational psychology to form a strong Islamic character. Using a qualitative method of literature study with primary source analysis, this research identifies that individual development is influenced by fitrah (innate potential), heredity, and environment (family, school, community). The results show that Islamic educational psychology plays a central role through internalization of values from an early age, the formation of an Islamic educational environment, habituation of positive behavior, alignment of faith-science-amal, optimization of the role of parents and teachers, use of productive technology, and evaluation and counseling. This strategy is expected to give birth to a smart generation, strong in faith and morals, and able to become agents of change for the realization of Islamic civilization.